Execution of Quality by Design Approach for Preparation and Optimization of Inclusion Complexes: In-vivo and ex-vivo Assessment. Issue 6 (2nd November 2022) - Bajwa, Neha; Singh, Preet Amol; Naryal, Srishti; Sharma, Trisha; Sijwal, Puran Singh; Baldi, Ashish
Abstract: The inclusion complex of α, β-arteether with β-cyclodextrin was prepared. The ratio was selected by implementing the QbD approach to get the best host-guest complex ratio. Further, the formation of the best complex was compared with stability analysis. Also, the enhancement in dissolution profile, as well as solubility, was compared with the pure α, β-arteether. The cyclodextrin derivative with maximum enhanced solubility and best dissolution profile was further used for PKPD modeling, permeability studies, and in-vivo and ex-vivo studies. By QbD approach as well as phase solubility studies it was confirmed that 1:1 fits best for the ART-CD inclusion complex formation. This was substantiated by a saturation solubility investigation, which found that in the presence of PVPK30, the solubility of α, β-arteether was enhanced by 77.05 times. The crystalline nature of the drug was lost or diminished greatly in the inclusion complex, showing the drug was present in a solubilized form in the formulation, according to scanning electron microscopy, X-ray diffraction, and differential scanning calorimetry. Further, the complex powder was converted into spheroids by the spheronization technique and filled in empty enteric-coated shells. In vitro release studies for spheroids-filled enteric capsules were carried out for 6 h by progressive dissolution technique. The pharmacokinetic model using Ecosim Pro 6.2.0 software confirms the enhancement of the bioavailability of the arteether. Further, the in vivo studies also confirm the enhancement in absolute bioavailability by 48.29% when compared with i.v. data of pure drugs. The complex shows an 11% maximum enhancement in antimalarial activity when compared with pure drugs. From the research, it was concluded that inclusion complexation is a suitable approach to improvise the solubility as well as bioavailability of hydrophobic drugs like α, β-arteether. GRAPHICAL ABSTRACT: UF0001